Foodborne Pathogens Management: From Farm and Pond to Fork (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents original research as well as reviews on current food safety issues. A wide range of biological hazards, food commodities and measures to assess, control and manage hazards are covered. With respect to food commodities, meat, milk/dairy and fish/seafood are covered, but also wild game and edible insects. The epidemiology of parasites and pathogenic bacteria (Clostridioides difficile and Listeria monocytogenes) in various food chains is reviewed, as well as the impact of food technology on food safety.